Mating Calls of Certain Philippine Anurans (Microhylidae, Ranidae) - Alcala, Angel C.; Joermann, Gerhard; Brzoska, Josef (Silliman Journal, 2024)
The mating calls of five Philippine anurans are analyzed. Kaloula picta and K. conjuncta, both belonging to the family Microhylidae, have stereotyped and simple-structured mating calls. The calls of these two species differ in temporal parameters. In contrast, three species of the family Ranidae–Rana erythraea, R. Signata and Ooeidozyga laevis–have more complex calis. Those of R. erythraea and Ooeidozyga laevis are very variable, each with-different call types, and that of R. signata contains only one type. The calls of these two erythraea include frequency-modulated tone pips and harmonic elements, while those of the other two ranids have mainly pulsed signals. Mating calls of these Philippine frogs may be used in clarifying taxonomic problems.